An Overview of Young Women's Knowledge of Menstrual Personal Hygiene - Jagentar Pane; Rotua Pakpahan; Sisri Nadeak (GLOBAL HEALTH SCIENCE GROUP, 2022)
Hygiene is very important for young women, especially during menstruation. Improper personal hygiene care will lead to the development of germs and infectious diseases, for that it is very necessary to maintain personal hygiene during menstruation to avoid disease.This study aims to determine the knowledge of young women regarding personal hygiene during menstruation at SMA Santo Mikhael Pangururan in 2022. This type of research is descriptive with a cross sectional approach. Researchers use a type of research that is descriptive and data collection at one time only. Researchers use all populations or all students are all students of class X as many as 95 people. The sampling technique used is total sampling. The analysis used is univariate analysis. The results obtained as many as 95 respondents, the majority had sufficient knowledge of 71 respondents (74.7%) and the minority have good knowledge and 12 people lacked knowledge(12.6%).Based on this research, it is expected that UKS will work together with local health centers to provide health education or promotion, especially personal hygiene during menstruation in order to increase the knowledge and awareness of young women regarding personal hygiene during menstruation.